2011
DOI: 10.1179/026708310x12668415533928
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mixed mode I/II on fracture behaviour of laminated metal matrix composites

Abstract: The effects of mixed mode loading (I/II) on the fracture toughness and fracture behaviour of both 6090/SiC/20p-6013 diffusion bonded laminates and 2080/SiC/20p-2080 adhesive bonded laminates tested in the crack arrester orientation were investigated. The effects of layer thickness and volume fraction ratio on the fracture behaviour under the mixed mode were also studied. The fracture behaviour under mode I/II of available similar discontinuously reinforced aluminium (DRA) materials was additionally compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Hence, it can be proposed that delamination and crack tip blunting are the principal components in improving the crack growth resistance of the LGCs. Hassan (32) has also showed similar crack deflection and improved fracture toughness in two-layer Al composites (2080/ 20%SiC p )/Al alloy (2080). Zechnera and Kolednik (33) showed that the introduction of a soft polymer layer in Al multilayer composites significantly improved the crack growth resistance.…”
Section: Layer-graded Cu/b 4 C/graphite Hybrid Composites 723mentioning
confidence: 85%
“…Hence, it can be proposed that delamination and crack tip blunting are the principal components in improving the crack growth resistance of the LGCs. Hassan (32) has also showed similar crack deflection and improved fracture toughness in two-layer Al composites (2080/ 20%SiC p )/Al alloy (2080). Zechnera and Kolednik (33) showed that the introduction of a soft polymer layer in Al multilayer composites significantly improved the crack growth resistance.…”
Section: Layer-graded Cu/b 4 C/graphite Hybrid Composites 723mentioning
confidence: 85%
“…The conventional Al/SiC p systems shown in Fig. 6 [2,23,26] exhibit little effects of mode mixity on the normalized total fracture energy, although the damage mechanisms in such composites are quite different than that exhibited presently, as discussed below.…”
Section: Discussionmentioning
confidence: 88%
“…In conventional Al/SiC p composites, damage typically takes the form of fractured SiC p particulates and/or SiC p /matrix interface decohesion [2,23,[26][27][28][29][30][31]. Fracture nucleation in such systems appears to depend on the normal/hydrostatic stress and damage evolves during tensile straining until catastrophic failure occurs via void link up through the matrix [28][29][30][31].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations